Role of Environmental Toxicants on Neurodegenerative Disorders - Nabi, Masarat; Tabassum, Nahida (Frontiers in Toxicology, 2022)
Neurodegeneration leads to the loss of structural and functioning components of neurons over time. Various studies have related neurodegeneration to a number of degenerative disorders. Neurological repercussions of neurodegeneration can have severe impacts on the physical and mental health of patients. In the recent past, various neurodegenerative ailments such as Alzheimer’s and Parkinson’s illnesses have received global consideration owing to their global occurrence. Environmental attributes have been regarded as the main contributors to neural dysfunction-related disorders. The majority of neurological diseases are mainly related to prenatal and postnatal exposure to industrially produced environmental toxins. Some neurotoxic metals, like lead (Pb), aluminium (Al), mercury (Hg), manganese (Mn), cadmium (Cd), and arsenic (As), and also pesticides and metal-based nanoparticles, have been implicated in Parkinson’s and Alzheimer’s disease. The contaminants are known for their ability to produce senile or amyloid plaques and neurofibrillary tangles (NFTs), which are the key features of these neurological dysfunctions. Besides, solvent exposure is also a significant contributor to neurological diseases. This study recapitulates the role of environmental neurotoxins on neurodegeneration with special emphasis on major neurodegenerative disorders such as Alzheimer’s and Parkinson’s disease.